2019
DOI: 10.1039/c8nr07269h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale organization of tetraspanins during HIV-1 budding by correlative dSTORM/AFM

Abstract: Membrane partition and remodeling play a key role in numerous cell mechanisms, especially in viral replication cycles where viruses subvert the plasma membrane to enter and escape from the host cell.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…We also used FCS to assess the molecular brightness of ADAM10/Tspan15 BiFC dimers, to estimate the degree of clustering. The existence of some traces containing a brighter Tspan15/ADAM10 component was indicative of larger cluster formation, as has been observed for TspanC8s and other tetraspanins by super-resolution microscopy (35)(36)(37). We propose that FCS imaging of BiFC dimers will be useful for the study of other tetraspanin/partner protein complexes.…”
Section: Discussionsupporting
confidence: 59%
“…We also used FCS to assess the molecular brightness of ADAM10/Tspan15 BiFC dimers, to estimate the degree of clustering. The existence of some traces containing a brighter Tspan15/ADAM10 component was indicative of larger cluster formation, as has been observed for TspanC8s and other tetraspanins by super-resolution microscopy (35)(36)(37). We propose that FCS imaging of BiFC dimers will be useful for the study of other tetraspanin/partner protein complexes.…”
Section: Discussionsupporting
confidence: 59%
“…We also used FCS to assess the molecular brightness of ADAM10/Tspan15 BiFC dimers, to estimate the degree of clustering. The existence of some traces containing a brighter Tspan15/ADAM10 component was indicative of larger cluster formation, as has been observed for TspanC8s and other tetraspanins by super-resolution microscopy (Zuidscherwoude et al 2015; Marjon et al 2016; Dahmane et al 2019). We propose that FCS imaging of BiFC dimers will be useful for the study of other tetraspanin/partner protein complexes.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies have shown the localization of tetraspanin proteins in specific regions of curved cell membranes. For instance, CD9 and its related tetraspanin, CD81, are localized in the growing tips of virus buds and involved in the infection cycle, and are directly implicated in generating membrane curvature 13,14 . Molecular shapes of membrane proteins are highly associated with the protein localization as well as membrane shaping and remodeling [15][16][17][18] .…”
Section: Resultsmentioning
confidence: 99%